International Trade Theory in Vintage Models - Smith, M. A. M. (Review of Economic Studies, 1976)
Journal Article International Trade Theory in Vintage Models Get access M. A. M. Smith M. A. M. Smith London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 43, Issue 1, February 1976, Pages 99–113, https://doi.org/10.2307/2296604 Published: 01 February 1976 Article history Received: 01 June 1974 Accepted: 01 April 1975 Published: 01 February 1976